2019
DOI: 10.1016/j.ssmph.2019.100410
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of long-term unemployment in early adulthood: A Finnish birth cohort study

Abstract: Cumulative contributions of social and health-related determinants to long-term unemployment during early working life among young adults are poorly understood. Therefore, we used four cumulative indices of both parental and own social and health-related determinants of such unemployment among a cohort which comprised a complete census of children born in Finland in 1987. The cohort participants were registered in the Medical Birth Register, and they were followed-up through 2015 (N = 46 521). We calculated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(51 reference statements)
2
10
1
Order By: Relevance
“…The former was a particularly strong predictor for the earlier entrees. This is also in line with previous studies 6,41 .…”
Section: Main Findingssupporting
confidence: 94%
See 1 more Smart Citation
“…The former was a particularly strong predictor for the earlier entrees. This is also in line with previous studies 6,41 .…”
Section: Main Findingssupporting
confidence: 94%
“…be linked to both parental and own socioeconomic position and health. Particularly social disadvantage and early mental disorders of parents and the offspring have been linked to both work disability and long-term unemployment of young adults 2,6 . As mental disorders increase already among young adults, even before entering paid employment, they need to be considered when focusing on work participation among young adults [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Entry into paid employment was based on age when the participants reported they had their first actual job, excluding summer jobs during education and other shorter training periods. Broadly following previous procedures [11,12], and reflecting a typical age to finish higher education (by 23 years) in Finland (for more details of the Finnish educational system, see e.g., https://minedu.fi/en/education-system), age at entry was classified into four groups distinguishing between early, average and late entry into first paid employment: ≤18 years, 19-21 years, 22-24 years (reference) and ≥25 years, respectively.…”
Section: Predictors: Timing Of Entry Into Paid Employment and Physicamentioning
confidence: 99%
“…Indeed, timing of entry into paid employment is potentially linked to a wide range of health-related outcomes including work (non-)participation, as a proxy indicator of health. A birth cohort study showed that those who had their first period of paid employment at an older age had higher odds for long-term unemployment over the follow-up [12]. Regarding behavior-related risk factors, smoking is more common among those who begin their work careers early, as compared to those who have acquired higher education and have therefore delayed entry into paid employment or starting a family [13].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-established that poor health is the most common barrier to extending working life [3,6,7]. People with a chronic disease are more likely to have more unstable work careers involving, for example, higher rates of unemployment and work disability in their early careers [8]. They spend more time on sick leave and disability retirement and retire earlier than people without chronic health problems [6,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%